The Effects of the Plyometric Exercise Training Program on Explosive Movement (Agility) on the Performance of Futsal Athletes (American Journal of Physical Education and Health Science, 2025)
This study employed quantitative research design specifically the quasi-experimental research design to compare the explosive movements of the control and experimental groups before and after intervention wherein the primary instrument was the Plyometric exercise training program adopted from Jsport Sci Med. 2006. The survey questionnaire was used that consisted of items that measure the acceptability and relevance of the training program and was rated by the athletes themselves. In data analysis, the researcher utilized the mean and standard deviation to determine the level of athletes’ agility performance before and after the training program. Additionally, analysis of covariance (ANCOVA) was used to examine the mean difference in participants’ post-performance as controlling for pre-performance agility. The study results showed a significant difference in agility’s post-performance between the two groups as controlled by the pre-performance. It is recommended that the coaches, trainers, and athletes may integrate the plyometric exercise training program during their training further to enhance athletes’ agility skill. It could serve as a guide for them to monitor the progress.